Hubungan Antara Opac Dengan Kebutuhan Informasi Pemustaka di Perpustakaan Politeknik Kesehatan Kementerian Kesehatan Padang - Muhammad zaki arif; Marlini Marlini (Journal of Creative Student Research, 2024)
Users find it difficult when using OPAC. This is because the collections displayed by OPAC are different from the shelf layout, causing users to look directly on the shelves more often than using OPAC. The aim of this research is to describe the relationship between OPAC and the information needs of users in the Health Polytechnic library of the Padang Ministry of Health. This type of research is a quantitative descriptive approach. The respondents in this study were 84 students using the Slovin formula with random sampling technique. The results of the research show that the correlation between variable X and variable Y is 0.398 with a significance of <0.05, so it can be said that Meanwhile, the R Square coefficient of determination was found to be 0.159, which means that the OPAC variable has an influence of 15.9% on information needs in the Padang Ministry of Health Polytechnic library.